Effect of geometric modification on flow behaviour and performance of reverse flow combustor. (March 2019) - Joy, J; Wang, PC; Yu, SCM
Numerical investigation had been performed on the reverse flow combustor of a mini gas turbine engine so as to investigate the performance characteristics of the combustor by means of geometry modifications. In order to enhance the thrust performance of the reverse flow combustor, the baseline combustor (Model A) was previously modified by increasing its chamber volume by 15%, the fuel-air ratio (FAR) by 40% and by raising the injection point density to two (Model B). However, the thrust optimization of the baseline combustor resulted in high combustor exit temperature that could potentially damage the combustor liners. To rectify the adversity of high exit temperature, the combustor cooling effects were achieved by subsequently adding additional passage holes at the dilution zone of the Model B combustor so as to direct the incoming cold flow from the compressor exit towards the outgoing hot flow in the reverse flow combustor (Model C). The commercial software ANSYS Fluent 17.0 was adopted in this study and to solve the turbulence model, Reynolds Averaged Navier–Stokes methodology was adopted by employing standard k-ɛ turbulence model with standard wall function. A probability density function model was generated to introduce the combustion species and a discrete phase Model was employed to specify the kerosene fuel-based injector properties. The numerical results of Model A combustor were validated against the previous experimental results using grid convergence test. The numerical results were observed to be in good agreement with the experimental results. However, ineffective mixing was found to be a setback for the baseline combustor (Model A) indicating the need for combustor performance improvement. The comparative results of the revised combustor model (Model C) showed that better cooling effects at the combustor exit could be achieved by adding supplementary passage holes at the downstream of the combustor outer liner, respectively. The addition of dilution holes also resolved the issue of high pressure loss that was observed in Model A combustor with no significant change in the specific fuel consumption. The present paper confirms that the performance of the reverse flow combustor model could be affected by slight geometric modification. The performance characteristics of the combustor models are presented in terms of thrust, thrust-to-weight ratio, specific fuel consumption, pressure loss and pattern factor.